The meaning-making of social impact in the academic and practitioners discourses - França, Nadir Raquel Cunha (2019)
The construct social impact has been shaping debates and supporting decision making in many segments of society. From research agendas in academia to the missions of corporations, social impact is easily presented as one of the centers of concern. Despite all this relevance, little is known about social impact\'s conceptual and paradigmatic approaches that frame the social impact academic research agenda and, similarly, the meaning-making processes that lead academics and practitioners\' understanding of social impact. This thesis fills this gap in three parts: first, by characterizing the academic research agenda on social impact over the years and building a snapshot of its paradigmatic orientation; second, by studying the academic discourse to understand the academic meaning-making processes of the social impact concept; third, by analyzing the discourse of practitioners from the Brazilian social finance ecosystem to unveil regularities and differences on their processes of signification of social impact and how these meanings affect their practices. To characterize the academic research agenda on social impact, I use bibliometric techniques and structured literature review. The contributions of this characterization are both the methodology applied and discussions on how social impact studies can advance. I show that research on social impact is rapidly expanding and integrate insights from environmental, social and economic related areas. Besides its interdisciplinary trait, the social impact research is mostly of positivist nature, especially interested in assessment. These results inform how social impact research can advance and proposes more subjective inquiries to complement the positivist studies, as more comprehensive approaches increase the potential for integrating scientific knowledge into decision making. To address the need for interpretative studies about social impact, I analyze the discourse of academic literature on social impact. To this end, I apply the social constructivist lenses and the sociology of knowledge approach to discourse (SKAD). The analysis shows that, at least, three different classifications of social impact emerge from the academic discursive construction: 1) social impact as a dynamic force; 2) social impact as a side-effect of development; and 3) social impact as a performance metric. Besides some expected differences across different research fields, I also observe regularities: social impact is perceived as measurable, multifaceted and interaction-dependent. Finally, these uncovered regularities, particularly in works related to social entrepreneurship that construct social impact as a metric of performance, puts social impact as the key concept that connects the actors in these scenarios. Thus, I also apply social constructivist lenses and SKAD to gain insights on the construction of social impact by Brazilian impact investors and social entrepreneurs. In summary, I find that differences in the meaning-making process of social impact influence the way in which social problems are understood, as well as the designing of solutions and, consequently, the metrics to assess such solutions. Also, I observe how different meaning-makings of social impact shape investor-investee relationships. This thesis concludes with guidelines on how future academic research, social impact investors and social entrepreneurs can benefit from the important aspects uncovered through the analysis of their discourses